Investing in resilience: A guide to climate risks and opportunities in Rwanda's key agricultural value chains - Wamicwe, Peter; Born, Lorna Erin; Grosjean, Godefroy; Newman, Richard; Mufti, Samaa; Burra, Dharani Dhar; Byandaga, Livingstone; Masika, Daniel; Derenoncourt, Ena; Gatsinzi, Patrick; Hientz, Lennart; Mbarushimana, Kagabo; et al. (2024)
Rwanda is at a pivotal moment, where agriculture—central to the country’s economy and rural livelihoods—holds the potential to drive resilience and prosperity. Yet, climate change presents serious challenges, threatening to disrupt agricultural productivity and increase food insecurity. In the face of these challenges, there is a significant opportunity to build a more sustainable and resilient agricultural sector for all Rwandans.